STRATEGIES USED IN THE CLASSROOM FOR SUPPORTING CHILDREN WITH AUTISM - Caushi, Kleona (European Scientific Journal, ESJ, 2014)
Autism is a life-long developmental disability that prevents people from understanding what they see, hear, and otherwise sense. This results in severe problems with social relationships, communication, and behavior. The Diagnostic and Statistical Manual of Mental Disorders, DSM-IV (American Psychiatric Association, 1994) defines autism as a pervasive developmental disorder characterized by: • Impairments in communication • Impairments in social interaction, and • Restricted, repetitive, and stereotypic patterns of behavior, interests, and activities. Children with Autism Spectrum Disorder (ASDs) handle information in their brain differently than other people. ASDs are “spectrum disorders.” That means ASDs affect each person in different ways, and can range from very mild to severe. Children with ASDs share some similar symptoms, such as problems with social interaction. But there are differences in when the symptoms start, how severe they are, and the exact nature of the symptoms. It is a spectrum condition, which means that, while all children with autism share certain difficulties, their condition will affect them in different ways. Some people with autism are able to live relatively independent lives but others may have accompanying learning disabilities and need a lifetime of specialist support. Children with autism may also experience over- or under-sensitivity to sounds, touch, tastes, smells, light or colors.